(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The large water network leads to a large set of nonlinear equations that need to be solved by either by Hard Darcy or Newton Raphson methods. Those two methods need a large code to analyze and simulate the network which takes large time. EPANET software can do a hydraulic analysis of the water network. In addition, the software can run with time duration which means that the result can be obtained as function in time. However, writing a code gives the result in the steady state manner because the Bernoulli’s equation was derived under the assumption of steady state. In this paper, a hydraulic analysis of water network of town of about 7000 population under an area of 0.6 km 2 and 2125 m 3 /day water demand is done by getting the nodal pressure, pipe discharge, and total head at the significant time hour of the day by using the EPANET software. Also, an optimization is done to minimize the energy cost of the electricity by the investigation of what minimum level that the tank discharge water without using a pump. Therefore, nine hours make the network operate by gravity main and 15 hours by pumping main. That can be done only by EPANET software result table that show how many hours that can make the pump off instead of using it the whole day. The energy cost minimized by 38 %.